Vertical distribution, composition profiles, sources and toxicity assessment of PAH residues in the reclaimed mudflat sediments from the adjacent Thane Creek of Mumbai. Issue 1 (15th May 2017) - Basavaiah, N.; Mohite, R.D.; Singare, P.U.; Reddy, A.V.R.; Singhal, R.K.; Blaha, U.
Abstract: A study on vertical distribution of magnetic susceptibility, carcinogenic and endocrine disrupting PAHs was performed in the reclaimed mudflat sediments adjacent to the Thane Creek of Mumbai. The 5-rings PAHs and ΣC-PAHs were more dominant at 120 cm depth contributing 52.23% and 60.19% respectively to ∑ PAHs. The average ratio values of LMW/HMW PAHs (0.58); Fla/(Fla + Pyr) (0.50); Ant/(Ant + Phe) (0.50); BaA/(Chry + BaA) (0.48); BaP/BghiP (2.06), Phe/Ant (1.03) and BaA/Chr (0.93) indicate that the PAH contamination might have raised due to inefficient combustion and pyrogenic emissions during the open burning of solid waste in the vicinity. This was further supported by the anthropogenic ferri(o)magnetic loading over the last 100 years influencing the Creek sediments. The PAHs toxicity estimation was performed by calculating the toxic equivalent quantity (TEQ) value of 8.62 ng TEQ/g which was below the safe level (600 ng TEQ/g) suggested by the Canadian risk-based soil criterion for protection of human health. Graphical abstract: Dense white smoke containing ash contaminated with toxic and other potentially carcinogenic compounds released from Deonar dumping ground in vicinity to reclaimed zone near Airoli industrial belt adjacent Thane Creek are carried off into the atmosphere. Highlights: Depth distribution of PAHs in reclaimed mudflat creek sediments studied 3-ring and high molecular weight PAHs (HMW PAHs) dominant at different depths ΣC-PAHs (carcinogenic PAHs) and HMW PAHs maximized at 120 cm. Toxicity assessment using toxic equivalent quantity for various C-PAHs